Novel Traits, Flower Symmetry, and Transcriptional Autoregulation: New Hypotheses From Bioinformatic and Experimental Data - Sengupta, Aniket; Hileman, Lena C. (Frontiers in Plant Science, 2018)
A common feature in developmental networks is the autoregulation of transcription factors which, in turn, positively or negatively regulate additional genes critical for developmental patterning. When a transcription factor regulates its own expression by binding to cis-regulatory sites in its gene, the regulation is direct transcriptional autoregulation (DTA). Indirect transcriptional autoregulation (ITA) involves regulation by proteins expressed downstream of the target transcription factor. We review evidence for a hypothesized role of DTA in the evolution and development of novel flowering plant phenotypes. We additionally provide new bioinformatic and experimental analyses that support a role for transcriptional autoregulation in the evolution of flower symmetry. We find that 5' upstream non-coding regions are significantly enriched for predicted autoregulatory sites in Lamiales CYCLOIDEA genes—an upstream regulator of flower monosymmetry. This suggests a possible correlation between autoregulation of CYCLOIDEA and the origin of monosymmetric flowers near the base of Lamiales, a pattern that may be correlated with independently derived monosymmetry across eudicot lineages. We find additional evidence for transcriptional autoregulation in the flower symmetry program, and report that Antirrhinum DRIF2 may undergo ITA. In light of existing data and new data presented here, we hypothesize how cis-acting autoregulatory sites originate, and find evidence that such sites (and DTA) can arise subsequent to the evolution of a novel phenotype.